(3TQM CQLhRI GHf SjfG aj GdWHs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3GdeOjfg s)
(3ChdgG (B:s
(3bGd CHh GdhdjO (B: (3CeG HYO MeO Gddg GdefYe HMjGI GdfahS aEfg PcQ HGdeLdS GdYGdi eLdS s
(3BNQgG (B:s
(3hbO aQZJ ef LejY GdYed hGdCf CbWY jbhd eced GMJjL Edi Gf jHbi YTQkG HYO GdTgQ CYdi CQHYjf jhekG s
(3hgh TQM Ydi CQLhRI GdQFjSs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs